2004
DOI: 10.1086/421526
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and Germline Instability of the ATTCT Repeat in Spinocerebellar Ataxia Type 10

Abstract: Spinocerebellar ataxia type 10 (SCA10) is an autosomal dominant disorder characterized by ataxia, seizures, and anticipation. It is caused by an expanded ATTCT pentanucleotide repeat in intron 9 of a novel gene, designated "SCA10." The ATTCT expansion in SCA10 represents a novel class of microsatellite repeat and is one of the largest found to cause human diseases. The expanded ATTCT repeat is unstably transmitted from generation to generation, and an inverse correlation has been observed between size of repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 38 publications
(43 reference statements)
2
41
0
Order By: Relevance
“…1,4,6 Yet, a separate Mexican-American family, where repeat interruptions were later identified, demonstrated anticipation but lacked the correlation between age at onset and repeat length. 6,8,14 Our current study has confirmed this lack of correlation and has also demonstrated it in additional families. This study highlights the presence of ATCCT repeat interruptions as a contributing factor in these disparate results.…”
Section: Discussionsupporting
confidence: 81%
“…1,4,6 Yet, a separate Mexican-American family, where repeat interruptions were later identified, demonstrated anticipation but lacked the correlation between age at onset and repeat length. 6,8,14 Our current study has confirmed this lack of correlation and has also demonstrated it in additional families. This study highlights the presence of ATCCT repeat interruptions as a contributing factor in these disparate results.…”
Section: Discussionsupporting
confidence: 81%
“…Although unstable trinucleotide repeats are the most common repeats that cause neurological disorders, other repeats, such as tetra-and pentanucleotides, may also expand, resulting in DM2 as well as SCA10 and SCA31. [9][10][11] Intragenically located expanded trinucleotide repeats exert their pathogenic effect on transcript and/or protein levels. For repeat mutations present in non-protein coding sequences, an RNA gain-of-function mechanism, which explains how transcripts of expanded alleles exert toxicity, has been proposed (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%
“…2 Inflicted patients typically have between 800-4,500 repeats, whereas unaffected people carry between 10-29 copies. 1,3 The symptoms include cerebellar atrophy, ataxia and seizures. 4 In patient-derived cells, the expanded ATTCT repeats are transcribed at the normal level and the pre-mRNA is processed normally, suggesting that the pentanucleotide repeat does not interfere with ATXN10 transcription.…”
Section: Introductionmentioning
confidence: 99%